1987
DOI: 10.1111/j.1471-4159.1987.tb01028.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Glucose Utilization: Comparison of [14C]Deoxyglucose and [6‐14C]Glucose Quantitative Autoradiography

Abstract: The [14C]deoxyglucose [Sokoloff et al., J. Neurochem. 28, 897-916 (1977)] and [6-14C]glucose [Hawkins et al., Am. J. Physiol. 248, C170-C176 (1985)] quantitative autoradiographic methods were used to measure regional brain glucose utilization in awake rats. The spatial resolution and qualitative appearance of the autoradiograms were similar. In resting animals, there was no significant difference between the two methods among 18 gray and three white matter structures over a fourfold range in glucose utilizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 36 publications
5
48
0
Order By: Relevance
“…This observation suggests that conditions which could cause increases in LCMR g 1u to above normal levels might be even less accu rately depicted by glucose. Recent observations that visual stimulation produced twofold increases in LCMR g 1u in some brain structures as determined with DG, compared to only 30% with [6-14C]glu cose, agree with this prediction (Collins et al, 1987).…”
Section: Discussionsupporting
confidence: 75%
“…This observation suggests that conditions which could cause increases in LCMR g 1u to above normal levels might be even less accu rately depicted by glucose. Recent observations that visual stimulation produced twofold increases in LCMR g 1u in some brain structures as determined with DG, compared to only 30% with [6-14C]glu cose, agree with this prediction (Collins et al, 1987).…”
Section: Discussionsupporting
confidence: 75%
“…The stability of 2-DG in the brain tissue, however, is less than previously assumed [30], since it has been shown that 10 min after the injection 2-DG is lost from the brain at a significant rate [11,12]. In any case, the direct comparison of metabolic rates assessed by the 2-DG and 14 C-glucose consumption revealed close correspondence between the two methods for many brain regions [9,10], and 2-DG appears to be a more sensitive marker of regional functional activation after sensory stimulation compared to 14 Cglucose [7][8][9]. Furthermore, the use of 2-DG enabled us to compare our results with previous reports [26,30,35].…”
Section: Experimental Protocol and Data Acquisitionmentioning
confidence: 68%
“…Discordant results obtained with [6- 14 C]glucose and [ 14 C]deoxyglucose were hypothesized to arise from upregulation of glycolysis, with increased [ 14 C]lactate production and release from activated structures (Fig. 1A) (Collins et al, 1987; Ackermann and Lear, 1989; Lear and Ackermann, 1989; Lear, 1990), a concept supported by rapid efflux of [ 14 C]lactate to blood during spreading cortical depression (Adachi et al, 1995; Cruz et al, 1999). Spreading and release of [ 14 C]glucose-derived label during acoustic activation of the inferior colliculus is reduced by inhibition of lactate transporters and astrocytic gap junctions (Cruz et al, 2007), supporting the importance of lactate release and implicating astrocytes in metabolite dispersal.…”
Section: Introductionmentioning
confidence: 86%
“…However, incomplete product trapping due to rapid release from activated tissue of labeled metabolites derived from [1- or 6- 14 C]glucose (Fig. 1A) causes underestimation (≥50%) of functional activation in different brain structures under normal stimulatory conditions compared to parallel studies with [ 14 C]deoxyglucose, which is metabolized mainly to [ 14 C]deoxyglucose-6-phosphate that is trapped intracellularly and not further metabolized by the glycolytic pathway (Sokoloff et al, 1977); undetected losses of labeled glucose metabolites also affects interpretation of results obtained under pathophysiological conditions, e.g., when excitatory activity is not reflected by label accumulation (Collins et al, 1987; Ackermann and Lear, 1989; Adachi et al, 1995; Cruz et al, 1999; Cruz et al, 2007). Discordant results obtained with [6- 14 C]glucose and [ 14 C]deoxyglucose were hypothesized to arise from upregulation of glycolysis, with increased [ 14 C]lactate production and release from activated structures (Fig.…”
Section: Introductionmentioning
confidence: 99%